2019
DOI: 10.1080/24748668.2019.1657655
|View full text |Cite
|
Sign up to set email alerts
|

Differences in approach run kinematics: successful vs. unsuccessful jumps in the pole vault

Abstract: This study investigated biomechanical differences between successful and unsuccessful jumps during a pole vault competition. Two hundred and seven pairs of successful and unsuccessful jumps at the same height were analysed. Participants included male and female athletes of three different age groups with bar height clearances ranging from 2.81 to 5.91 m. Run-up parameters were collected using an Optojump Next system and a Stalker Pro II radar gun. A 2D kinematical analysis was conducted to obtain selected para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…As well as providing for a comparison between elite-standard men and women pole vaulters, the values found show the kinematic characteristics of world-class performances that can be used by coaches. Many of these values were in line with what previous research has found (e.g., Linthorne and Weetman, 2012;Schade and Arampatzis, 2012;Cassirame et al, 2019;Panoutsakopoulos et al, 2021), and supports our understanding of pole vault mechanics by fortifying the current body of research on the event. However, there were also some results that differed from previous studies or, at least, highlighted some exceptions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As well as providing for a comparison between elite-standard men and women pole vaulters, the values found show the kinematic characteristics of world-class performances that can be used by coaches. Many of these values were in line with what previous research has found (e.g., Linthorne and Weetman, 2012;Schade and Arampatzis, 2012;Cassirame et al, 2019;Panoutsakopoulos et al, 2021), and supports our understanding of pole vault mechanics by fortifying the current body of research on the event. However, there were also some results that differed from previous studies or, at least, highlighted some exceptions.…”
Section: Discussionsupporting
confidence: 89%
“…The women's mean mass was 75% of the mean mass for men, and the lower relative strength of women and the restricting effect of pole mass on velocity (Angulo-Kinzler et al, 1994;Frère et al, 2010) might have influenced their decision to take fewer run-up steps in trying to prevent excessive deceleration toward the end of the run-up. The absolute spatial differences in men's and women's pole vaulting, including grip height and take-off CM height, suggest that there is a sex-based difference in the model for success in the event (Cassirame et al, 2019). This is unsurprising given how the chosen pole's length and mass must accommodate the athlete's stature and strength.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results confirmed the ability of elite pole vaulter to cope efficiently with the unbalanced related to pole carriage, but adding further constraints (PPS and TK) led to a progressive increase in asymmetry. However, these changes in asymmetry did not seem to be at the expense of the speed changes between the conditions and even less of performance (Cassirame et al, 2019). As found in previous studies, pole carriage and more generally extra-weight or arm swing restriction decreased the step length (Frère et al, 2009;Cross, Brughelli, & Cronin, 2014;Macadam, Cronin, & Feser, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…To achieve the best possible performance, athletes have to transfer the maximum of energy from their approach run to the pole and use energy recoil to elevate their centre of mass as high as possible (Arampatzis, Schade, & Brüggemann, 2002;Linthorne & Weetman, 2012;Schade & Arampatzis, 2012;Schade, Arampatzis, & Brüggemann, 2006). Several previous studies demonstrated a strong relationship between the horizontal take-off speed and performance in pole vault (Cassirame et al, 2019;Decker & Bird, 2008;Linthorne & Weetman, 2012;Steinacker, 1991). Basically, speed is growing during the run-up phase, and the related kinetic energy is then transferred into the bending pole.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of unsuccessful high jumps could yield important information about the factors contributing to suboptimal performance. While successful (SU) and unsuccessful (UN) jump comparisons have been undertaken for other events ( 18 ), key performance parameters in the high jump have mainly been identified by comparing SU jumps of different heights ( 6 , 9 , 19 ). As such, limited information exists on the magnitude and type of changes made by athletes to bring about successful bar clearance following an unsuccessful jump.…”
Section: Introductionmentioning
confidence: 99%